2002
DOI: 10.1016/s0893-133x(01)00305-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of Central Injection of Recombinant Rat Interleukin-4 on Lipopolysaccharide-Induced Sickness Behavior in Rats

Abstract: Systemic administration of the bacterial endotoxin lipopolysaccharide (LPS) has profound depressive effects on behavior that are mediated by the inducible expression of pro-inflammatory cytokines, such as interleukin-1 (IL-1), IL-6 and tumor necrosis factor ␣ (TNF), in the brain. To assess the regulatory effects of the anti-inflammatory cytokine IL-4 on LPS-induced sickness behavior, rats injected intra-peritoneally (i.p.) with LPS were administered intracerebroventricularly (i.c.v.) with When an organism b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 62 publications
4
26
0
Order By: Relevance
“…IL-4 appears to inhibit the classical activation of astrocytes in vivo. In our neuroinflammation model, pretreatment with IL-4 abolished LPS-induced gene expression and improved motor impairment in vivo, which is in line with previous findings that IL-4 attenuated LPS-induced proinflammatory cytokines and sickness behaviors (51). Therefore, classical or alternative activation stimuli seem to induce respective phenotypic changes and inhibit opposite phenotypes in astrocytes.…”
Section: Discussionsupporting
confidence: 91%
“…IL-4 appears to inhibit the classical activation of astrocytes in vivo. In our neuroinflammation model, pretreatment with IL-4 abolished LPS-induced gene expression and improved motor impairment in vivo, which is in line with previous findings that IL-4 attenuated LPS-induced proinflammatory cytokines and sickness behaviors (51). Therefore, classical or alternative activation stimuli seem to induce respective phenotypic changes and inhibit opposite phenotypes in astrocytes.…”
Section: Discussionsupporting
confidence: 91%
“…1 A shows that IGF-1 administered peripherally improved recovery from LPS-induced sickness in wild-type but not in db͞db mice. Previous studies by us (57)(58)(59)(60) have shown that the antiinflammatory cytokines IL-1RA and IL-10 can down-regulate sickness, but these have all been administered i.c.v. Equally important is that db͞db mice were resistant to the sicknessimproving features of IGF-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After 30 min, nonadherent cells were removed by washing twice with growth medium. Remaining cells were at least 80% macrophages confirmed by CD11b staining and morphology (50).…”
Section: Peritoneal Macrophage Isolationmentioning
confidence: 91%